Bringing Trans-Women “Back to Fitrah”: Islamic (Re)education/ Rehabilitation Projects and Discourses in Malaysia - Biro, Timea (Taylor and Francis, 2023)
This chapter discusses state-Islamic (re)education/rehabilitation programs targeted at transgender Muslim individuals declared to be “deviant” by the authorities in Malaysia. It explores government policies/perspectives, as well as narrated lived experiences of transgender people, and the interfaces between the two, ultimately to address questions of equity and injustice stemming from attempts of re(education)/rehabilitation. The chapter demonstrates how trans-people maintain multiple ways of navigating the various programs and coercive discourses that aim to educate, define, and categorize them. Various ways of meaning-making and self-acceptance help to realize alternative transgender-subjectivities despite exposure to the re(education). This demonstrates precisely what the official position claims is missing among the transgendered: that is, deep religious faith.
CRIS-Team Scopus Importer:2023-07-28